Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1017/s0007485300038700
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in oviposition aggregation pheromone composition within the Simulium damnosum (Diptera: Simuliidae) species complex

Abstract: The oviposition aggregation pheromone of six species or forms of the Simulium damnosum Theobald complex (Diptera: Simuliidae) from different sites in West Africa, was investigated by gas chromatographic analysis of hexane extracts of the ovaries from wild-caught flies, bloodfed and maintained until gravid in the laboratory. The two compounds previously shown to be released from fresh eggs and associated with mediation of oviposition aggregation were found in S. leonense

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
(46 reference statements)
1
8
0
1
Order By: Relevance
“…Fig. 1) occurred consistently in volatile collections and ovary extracts, in all species studied within this species complex, and that those peaks were associated with attraction of site seeking ovipositing flies (McCall, 1995;McCall et al, 1997). In the multiple choice bioassay results presented here, the fraction containing these two compounds, fraction 3, attracted a signdicantly greater number of ovipositions than any other fraction, confirming the role of these two compounds as constituents of the oviposition aggregation pheromone.…”
Section: Discussionsupporting
confidence: 73%
“…Fig. 1) occurred consistently in volatile collections and ovary extracts, in all species studied within this species complex, and that those peaks were associated with attraction of site seeking ovipositing flies (McCall, 1995;McCall et al, 1997). In the multiple choice bioassay results presented here, the fraction containing these two compounds, fraction 3, attracted a signdicantly greater number of ovipositions than any other fraction, confirming the role of these two compounds as constituents of the oviposition aggregation pheromone.…”
Section: Discussionsupporting
confidence: 73%
“…muscid, calliphorid, and scarcophagid flies) (43, 218) or by pheromonal or microbial odor stimuli associated with conspecific females at feeding or oviposition sites (e.g. simuliid, psychodid, calliphorid, and anthomyiid flies) (18,59,117,148,206). Conversely, after oviposition, females of tephritid, agromyzid, and other anthomyiid species deposit host-marking pheromone, which deters repeated egg laying at sites that can support only a limited number of larvae (158,178,198).…”
Section: Dipteramentioning
confidence: 99%
“…Furthermore described a sample of 20 flies as being 'dark' and belonging to the forest group. McCall et al (1997) used some flies from Bioko in their analysis of oviposition aggregation pheromone and concluded that the composition of the pheromone was similar throughout the S. damnosum complex.…”
Section: Introductionmentioning
confidence: 99%